Aspectos taxonômicos, ecológicos e evolutivos em drosofilídeos neotropicais - Machado, Stela (2015)
Drosophila melanogaster is a known model organism that has prompted studies in diverse fields of knowledge and helped in the scientific advance of several fields. However, Drosophilidae, the family in which this species is inserted, is extremely speciose, being composed by more than 4,200 species, most of which with deficient or absent knowledge, besides many unknown species. Even hypothesis concerning the evolution of the group which were formulated in 1975 were not yet properly tested. Therefore, the present thesis aims to fill some of these gaps by testing the hypothesis of radiation proposed by THROCKMORTON (1975) in different taxonomic groups of drosophilids, in order to determine if they evolved through adaptative radiations or are merely taxonomic groups with difficult phylogenetic resolution. So, in chapter 1, species encompassing the virilis-repleta and tripunctata lineages of the Drosophila subgenus were used, and the results have shown that the evolution of this group is more complex than previously proposed, with the first lineage presenting signs of niche conservatism and the second being compatible with the occurrence of an adaptive radiation. In chapter 2, we also found signs of abiotic niche conservatism between mycophylic species belonging to Zygothrica genus group that use fungal fruitification bodies as resource for feeding, oviposition and/or breeding. Also in this chapter, we contributed to the knowledge of the family diversity by expanding the records and modeling the potential distribution of several species of Hirtodrosophila, Paraliodrosophila, Mycodrosophila and Zygothrica recorded in Brazil. Besides, through the niche modeling approach, we showed that some species of these genera seem to be susceptible to the world climatic changes due to the abiotic factors which limit their distribution and the response curves presented by each species. In chapter 3, we explored the diversity of species of the Zygothrica genus group and the effectiveness of the DNA barcode methodology in their taxonomic exploitation. In this case, we demonstrated the presence of a great cryptic diversity of representatives of the Zygothrica genus group in the Neotropics, with the record of at least 24 putative new species. Besides, we also showed the huge potential of this methodology in the identification and species discovery in this group. In chapter 4, we explored the Mycodrosophila genus, principally the M. projectans complex, which showed to be an interesting group to the study of speciation due to the frequent presence of the cryptic diversity in sympatry and syntopy. These works highlighted how much some interesting aspects and groups of Drosophilidae have been neglected, and call attention to the fact that these are fundamental aspects to the understanding of taxonomy, ecology and evolution not just of the focused groups, but also of the premier model species of evolutionary biology, D. melanogaster.